If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 62 + -3x = 2x + 7 Reorder the terms: 62 + -3x = 7 + 2x Solving 62 + -3x = 7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 62 + -3x + -2x = 7 + 2x + -2x Combine like terms: -3x + -2x = -5x 62 + -5x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 62 + -5x = 7 + 0 62 + -5x = 7 Add '-62' to each side of the equation. 62 + -62 + -5x = 7 + -62 Combine like terms: 62 + -62 = 0 0 + -5x = 7 + -62 -5x = 7 + -62 Combine like terms: 7 + -62 = -55 -5x = -55 Divide each side by '-5'. x = 11 Simplifying x = 11
| 135+3v=(25+5)+3v | | 8u-11=u+67 | | 12x^3+6x^2+20x^2+10x=0 | | 4x-8x+14=0 | | x^4+2x^3+27x+54=0 | | x+3=1+1 | | 61.25=35+.15t | | 5(3Z-1)-3(Z+9)=5(Z+1) | | 30+5x=15+10x | | 5(4Z-1)-4(Z+4)=13(Z+1) | | 3x^2-7x-3=x | | 13-10x=73-24x | | 28=3x-7 | | 9+9m-1=8m+32-3m | | x*.04+x=74000 | | 5m-2(m+1)=m-1 | | 52-3x=7x-22 | | 3+8(2-9m)= | | 830=117x-233630 | | Y=10-2x | | 9x^2+5x+4= | | P+(-9)=-5 | | 4*(12-x)=-4 | | 2(x+5)=12 | | 52=-48+m | | -9+d=15 | | 5x-19=-6 | | 4s^2=7s | | 2x+13=41 | | 2w^2-13+18=0 | | 60x+30(15-x)=600 | | 1/2(x-5)-1=2/3(x-6) |